Anxiety is more common in children with asthma. Issue 8 (3rd June 2010) - Vuillermin, P J; Brennan, S L; Robertson, C F; Carlin, J B; Prior, M; Jenner, B M; South, M
Abstract : Objective: There are a variety of reasons why there may be an association between asthma and anxiety in children. Research into the relation between asthma and anxiety has been limited by the sole use of parent-reported or self-reported asthma symptoms to define asthma status. The objective of this study was to determine if children with physician-defined asthma are more likely to suffer anxiety than children without asthma. Design: A population-based, cross-sectional assessment, of self-reported anxiety symptoms. Setting and participants: Children aged 5–13 years from Barwon region of Victoria, Australia. Asthma status was determined by review with a paediatrician. Controls were a sample of children without asthma symptoms (matched for age, gender and school). Outcome measure: The Spence Children's Anxiety Scale (SCAS) written questionnaire. The authors compared the mean SCAS score, and the proportion of children with an SCAS score in the clinical range, between the groups. Results: Questionnaires were issued to 205 children with asthma (158 returned, response rate 77%), and 410 controls (319 returned, response rate 78%). The SCAS scores were higher in asthmatics than controls (p<0.001); and were more likely to be in the clinical range (OR=2.5, 95% CI 1.1 to 5.8, p=0.036). There was no evidence that these associations could be explained by known confounding factors. Conclusions: Children with asthma are substantially more likely to suffer anxiety than children without asthma. Future studies are required to determine the sequence of events that leads to this comorbidity, and to test strategies to prevent and treat anxiety among children with asthma.